Personality Traits and Postnatal Depression: The Mediated Role of Postnatal Anxiety and Moderated Role of Type of Birth - Roman, Maria; Bostan, Cristina Maria; Diaconu-Gherasim, Loredana R.; Constantin, Ticu (Frontiers in Psychology, 2019)
This study investigated how personality traits are related to postnatal depression two weeks after giving birth and whether these relations are mediated by postnatal anxiety, measured after 3-4 days after giving birth and moderated by the type of birth. New mothers (N = 672, Mage = 29.33) completed scales assessing their personality traits, postnatal anxiety and postnatal depression three or four days after giving birth (T1). They also reported postnatal depression two weeks after giving birth (T2). Path analysis indicated that postnatal anxiety explained the link between personality traits (i.e., neuroticism) and postnatal depression two weeks after childbirth. The type of birth moderated the relation among, personality traits, postnatal anxiety and depression. Neuroticism and consciousness, in the natural birth’s group, and neuroticism and agreeableness, in the cesarean birth’s group, were associated with postnatal depression. Further, anxiety explained the relation between neuroticism and postnatal depression in both natural and cesarean birth groups. In addition, postnatal anxiety mediated the relation between extraversion and postnatal depression in the cesarean birth group. Our findings highlight that postnatal anxiety is a potential mechanism explaining how personality traits (i.e., neuroticism, extraversion) are related to postnatal depression, and that these relations may depend on the type of childbirth.